2022
DOI: 10.1101/2022.06.29.497865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of lactate metabolism in the peripheral nervous system leads to motor-selective deficits

Abstract: Schwann cells (SCs) myelinate and provide trophic support to axons in the peripheral nervous system (PNS) and disruption of SC cellular metabolism leads to demyelination and axon degeneration, both symptoms of peripheral neuropathies. The lactate shuttle hypothesis proposes that glycolytic support cells supply lactate to adjacent axons to sustain their high metabolic demands, a process that requires the interconversion of lactate and pyruvate via lactate dehydrogenase (LDH) in both SCs and neurons. To test thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…However, Cnp Cre mice also recombine Schwann cells and off‐target in subsets of CNS neurons including motoneuronal precursors (Genoud et al, 2002; Jo et al, 2021; Tognatta et al, 2017) (Figure S1a–e). The deletion of Ldh genes in Schwann cells and motoneurons causes a marked neuropathology (Bloom et al, 2022). Thus, we refrained from the histopathological analysis of brain and spinal cord of Ldha flox/flox ; Ldhb flox/flox ; Cnp Cre double mutant mice (hereafter referred to as dKO, Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…However, Cnp Cre mice also recombine Schwann cells and off‐target in subsets of CNS neurons including motoneuronal precursors (Genoud et al, 2002; Jo et al, 2021; Tognatta et al, 2017) (Figure S1a–e). The deletion of Ldh genes in Schwann cells and motoneurons causes a marked neuropathology (Bloom et al, 2022). Thus, we refrained from the histopathological analysis of brain and spinal cord of Ldha flox/flox ; Ldhb flox/flox ; Cnp Cre double mutant mice (hereafter referred to as dKO, Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Concomitantly, it was recently shown that targeting mitochondria with a small molecule could improve upper motor neuron health in a TDP-43 mouse model (Gautam et al, 2023) . The inability of ALS motor neurons to respond to high energy drains and the lack of compensatory glycolysis could render the motor neurons intrinsically more vulnerable as well as more dependent on glial support (Joseph Bloom et al. ; Lee et al, 2012) .…”
Section: Discussionmentioning
confidence: 99%
“…Axons receive energy support via Schwann cells that shuttle lactate via monocarboxylate transporters to the axons 36 . Change in Schwann cell metabolism or lactate shuttling can cause deficits in axonal maintenance 37‐41 . Addition of exogenous L‐Lactate can therefore compensate for deficits in Schwann cell metabolic support to axons 36 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Change in Schwann cell metabolism or lactate shuttling can cause deficits in axonal maintenance. [37][38][39][40][41] Addition of exogenous L-Lactate can therefore compensate for deficits in Schwann cell metabolic support to axons. 36 We tested this in our model, but lactate supplementation did not attenuate axonal changes.…”
Section: Secondary Axon Degeneration Is Prevented By Axonal Calpain I...mentioning
confidence: 99%